2014
DOI: 10.5897/ajmr2013.6584
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of chitosan-silver nanoparticle composite against Colletotrichum gloeosporioides associated with mango anthracnose

Abstract: Chitosan loaded with various metal ions such as Ag + , Cu 2+ , Zn 2+ , Mn 2+ and Fe 2+ has been reported to exert strong antimicrobial activity. In this study, the silver-nanoparticles (AgNPs) were synthesized at 95°C using chitosan as the reducing agent and stabilizer. The UV-Vis spectrum displayed peak in a range between 415-420 nm, the characteristic surface plasmon resonance band of silver nanoparticles. The size, shape and aggregation properties of the resultant nanoparticles were examined using field emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For example, A-Ag NPs improve the shelf-life of lime (Citrus aurantifolium) and apple (Malus domestica) [113]. Another study conducted by Chowdappa [114] noted that chitosan-based Ag-NPs composites greatly minimize post-harvest losses in fresh mangoes and also boost quality because of their anti-fungal properties. Kumar et al [115] observed that Ag-NPs, along with biocompatible coating materials such as chitosan and glycol, improved the storage duration of red grapes up to 14 days.…”
Section: Silver (Ag) Nanoparticlesmentioning
confidence: 99%
“…For example, A-Ag NPs improve the shelf-life of lime (Citrus aurantifolium) and apple (Malus domestica) [113]. Another study conducted by Chowdappa [114] noted that chitosan-based Ag-NPs composites greatly minimize post-harvest losses in fresh mangoes and also boost quality because of their anti-fungal properties. Kumar et al [115] observed that Ag-NPs, along with biocompatible coating materials such as chitosan and glycol, improved the storage duration of red grapes up to 14 days.…”
Section: Silver (Ag) Nanoparticlesmentioning
confidence: 99%
“…Ag NPs show a particularly strong bactericidal performance: with silver additions, the textile has antimicrobial activities, while thin films coated on the substrate have an antifungal function. Chowdappa [10] reported that chitosan-AgNP composite exhibits a higher antifungal activity against C. gloeosporioides than its components [11]. The biological activity of metallic glass materials has also attracted significant attention in recent years [12,13].…”
Section: Introductionmentioning
confidence: 99%